High-resolution melting analysis for prenatal diagnosis of beta-thalassemia in northern Thailand - Charoenkwan P. (2017)
© 2017 The Japanese Society of Hematology High-resolution melting (HRM) analysis is a rapid mutation analysis which assesses the pattern of reduction of fluorescence signal after subjecting the amplified PCR product with saturated fluorescence dye to an increasing temperature. We used HRM analysis for prenatal diagnosis of beta-thalassemia disease in northern Thailand. Five PCR–HRM protocols were used to detect point mutations in five different segments of the beta-globin gene, and one protocol to detect the 3.4 kb beta-globin deletion. We sought to characterize the mutations in carriers and to enable prenatal diagnosis in 126 couples at risk of having a fetus with beta-thalassemia disease. The protocols identified 18 common mutations causing beta-thalassemia, including the rare codon 132 (A–T) mutation. Each mutation showed a specific HRM pattern and all results were in concordance with those from direct DNA sequencing or gap-PCR methods. In cases of beta-thalassemia disease resulting from homozygosity for a mutation or compound heterozygosity for two mutations on the same amplified segment, the HRM patterns were different to those of a single mutation and were specific for each combination. HRM analysis is a simple and useful method for mutation identification in beta-thalassemia carriers and prenatal diagnosis of beta-thalassemia in northern Thailand.